2015
DOI: 10.1080/13803395.2015.1117058
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of neuropsychological characteristics of very mild and mild dementia with Lewy bodies

Abstract: In the present work we found that faster progression to the mild DLB stage in the first few years of the disease is mainly related to deterioration of memory, attention/executive functions, and visuospatial abilities, as well as an increased frequency of visual hallucinations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
7
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 32 publications
6
7
0
1
Order By: Relevance
“…Verbal dynamic performance in the PDD group was modulated by dopaminergic stimulation; this modulation did not extend to nonverbal design fluency or other cognitive functions assessed, suggesting that this may be a relatively specific effect on verbal output. Taken together, our findings are in line with previous evidence for impaired organization of language output in parkinsonism (Petrova et al, 2016) but suggest a more specific limitation of verbal generation. Besides corroborating previous work showing reduced verbal fluency in parkinsonism (Herrera, Cuetos, & Ribacoba, 2012), the profiles of verbal adynamia exhibited by both our patient groups were broadly in keeping with the findings documented in previous detailed case studies of patients with PSP and dynamic aphasia (Esmonde et al, 1996; Robinson et al, 2006; Robinson et al, 2015).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Verbal dynamic performance in the PDD group was modulated by dopaminergic stimulation; this modulation did not extend to nonverbal design fluency or other cognitive functions assessed, suggesting that this may be a relatively specific effect on verbal output. Taken together, our findings are in line with previous evidence for impaired organization of language output in parkinsonism (Petrova et al, 2016) but suggest a more specific limitation of verbal generation. Besides corroborating previous work showing reduced verbal fluency in parkinsonism (Herrera, Cuetos, & Ribacoba, 2012), the profiles of verbal adynamia exhibited by both our patient groups were broadly in keeping with the findings documented in previous detailed case studies of patients with PSP and dynamic aphasia (Esmonde et al, 1996; Robinson et al, 2006; Robinson et al, 2015).…”
Section: Discussionsupporting
confidence: 93%
“…Verbal fluency deficits are well described in PD and are likely in part to reflect motor slowing together with executive compromise. Such deficits may also signify the involvement of language generation mechanisms and may help differentiate parkinsonian disorders, potentially while clinical disease is still mild (Petrova et al, 2016; Rittman et al, 2013). …”
Section: Introductionmentioning
confidence: 99%
“…More precisely, they scored lower than HCs in verbal production (i.e., formal semantic evocation) as well as in oral naming. These results are in line with some studies (e.g., [28, 63]) but contrast with studies showing a relative preservation of naming abilities in DLB (e.g., [64]). However, when language difficulties are present, the underlying mechanisms are not fully elucidated [16].…”
Section: Discussionsupporting
confidence: 89%
“…These findings are in line with the suggestion that impairment in non-memory domains (e.g., executive function, visuospatial abilities) is more likely to progress to DLB than single-domain amnestic mild cognitive impairment (MCI) [25, 27]. Researchers in a recent study assessed cognition in mild and very mild DLB [28]. The authors found that very mild DLB was associated with impairment of attentional/executive, visuospatial, visuoconstructive and naming abilities, as well as with difficulties in retrieval of episodic memory.…”
Section: Introductionsupporting
confidence: 80%
“…The pattern of verbal-learning deficits in RBD patients reported by Marchand(Marchand et al 2016) is similar to that reported in PD and mild DLB patients(Costa et al 2014, Petrova et al 2016). Adding a visuospatial task to the neuropsychological assessment increases the ability to predict the conversion to dementia in RBD patients, which is consistent with the prominent attention/executive functions and visuospatial declines noted early in DLB patients and in PD patients at risk of dementia(Goldman and Postuma 2014).…”
Section: Factors In Prediction Of Phenoconversion To Alpha-synucleinosupporting
confidence: 87%